East of Eden Television Production Still - Barney Rosenzweig Productions; Mace Neufeld Productions; Viacom Productions:::Creator::::::::::::
Aron Trask (Hart Bochner) standing next to Abra Bacon (Karen Allen), both looking down at Cal Trask (Sam Bottoms), who is lying on the runner board of what appears to be a 1917 Ford Model 'T,' in the 1981 television movie of 'East of Eden.' Digital copy only. No hard copy.